Selenotranscriptome Network in Non-alcoholic Fatty Liver Disease - Day, Kaitlin; Seale, Lucia A.; Graham, Ross M.; Cardoso, Barbara R. (Frontiers in Nutrition, 2021)
Observational studies indicate a negative role for selenium in the pathogenesis of non-alcoholic fatty liver disease (NAFLD). Transcriptomic exploration of the aetiology and progression of NAFLD may offer insight into the role selenium plays in this disease. This study compared gene expression levels of known selenoprotein pathways between individuals with a healthy liver to those with NAFLD. Publicly available gene expression databases were searched for studies that measured global gene expression in liver samples from patients with steatosis and nonalcoholic steatohepatitis (NASH) and healthy controls (with [HOC] or without [HC] obesity). A subset of five selenoproteins-related pathways (164 genes) were assessed in the four datasets included in this analysis. The gene TXNRD3 was less expressed in both disease groups when compared with HOC. SCLY and SELENOO were less expressed in NASH when compared with HC. SELENOM, DIO1, GPX2 and GPX3 were highly expressed in NASH when compared to HOC. Disease groups had lower expression of iron-associated transporters and higher expression of genes en-coding the ferritin sub-units. Our bioinformatics analysis suggests that the NAFLD liver may have lower selenium levels than a disease-free liver, as well as a disrupted iron metabolism. Our find-ings indicate that gene expression variation may be associated with the progressive risk of NAFLD.